2000
DOI: 10.2307/749889
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of the Total of Two Dice

Abstract: Many studies have shown that the strategies used in making judgments of chance are subject to systematic bias. Concerning chance and randomness, little is known about the relationship between the external structuring resources, made available for example in a pedagogic environment, and the construction of new internal resources. In this study I used a novel approach in which young children articulated their meanings for chance through their attempts to “mend” possibly broken computer-based stochastic gadgets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
17

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 9 publications
7
100
0
17
Order By: Relevance
“…Another methodological point to be discussed refers to the influence of the nature and the structure of a particular task in probabilistic reasoning (Nikiforidou and Pange 2009;Pratt 2000;Skoumpourdi et al 2009;Spinillo 2002). Responses and participation depend on the material, the stimuli, the design of the activity, the nature of random generators and the goal-context.…”
Section: Discussionmentioning
confidence: 99%
“…Another methodological point to be discussed refers to the influence of the nature and the structure of a particular task in probabilistic reasoning (Nikiforidou and Pange 2009;Pratt 2000;Skoumpourdi et al 2009;Spinillo 2002). Responses and participation depend on the material, the stimuli, the design of the activity, the nature of random generators and the goal-context.…”
Section: Discussionmentioning
confidence: 99%
“…Aspinwall and Shaw, (2000), Castro (1998), Gates (1981), Nilsson (2007;), Polaki (2002), Pratt (2000, Tatsis et al (2008) showed that students are more interested in probability contents, their perceptions and conceptual understanding if they are provided with concrete materials.…”
Section: Results Of the Teaching Approachmentioning
confidence: 99%
“…Κάποιες από αυτές τις μελέτες έχουν καταδείξει ότι ακόμη και μικρά παιδιά μπορούν να αναπτύξουν ισχυρή διαισθητική σκέψη για σημαντικές έννοιες της στατιστικής συμπερασματολογίας μέσα από την χρήση κατάλληλων εργαλείων εξεικοTνισης (visualisation) στατιστικών δεδομένων (e.g. Pratt, 2000 . Stohl & Tarr, 2002 .…”
Section: ο ρόλος των δυναμικών στατιστικών λογισμικών στην ανάπτυξης unclassified